2022
DOI: 10.1177/10760296221128294
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of non-Alcoholic Fatty Liver Disease and Associated Factors in Patients with Moderate or Severe Hemophilia: A Multicenter-Based Study

Abstract: Introduction Liver health is essential for persons with hemophilia (PWH) in order to maintain access to new therapies, such as gene therapy. Non-alcoholic fatty liver disease (NAFLD) is seldom reported in the hemophilia population. The study aimed to investigate the prevalence of NAFLD and associated factors in PWH. Methods Data of this cross-sectional study were obtained from a multicenter collaborative registry database. Results A total of 163 moderate or severe PWH with a complete data of liver examination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“… 11 , 33 Accordingly, 38% and 8% of patients in our series were overweight and obese, respectively, which increases the risk of diabetes, dyslipidemia, arterial hypertension, and, ultimately, NAFLD, which is the liver expression of the metabolic syndrome. 33 , 34 We also found that, although the vast majority had a minimal to moderate alcohol intake, 12% of the whole cohort were heavy drinkers (≥14 AUs per week), which is a risk factor for such systemic complications as chronic hepatitis/cirrhosis. 31 , 35 …”
Section: Discussionmentioning
confidence: 67%
“… 11 , 33 Accordingly, 38% and 8% of patients in our series were overweight and obese, respectively, which increases the risk of diabetes, dyslipidemia, arterial hypertension, and, ultimately, NAFLD, which is the liver expression of the metabolic syndrome. 33 , 34 We also found that, although the vast majority had a minimal to moderate alcohol intake, 12% of the whole cohort were heavy drinkers (≥14 AUs per week), which is a risk factor for such systemic complications as chronic hepatitis/cirrhosis. 31 , 35 …”
Section: Discussionmentioning
confidence: 67%
“…Although the exact root cause of the increase in FVIII levels in liver diseases is not known, there are several hypotheses regarding why FVIII levels changed [ 175 , 176 , 177 ]. The release of cytokine from necrotic cirrhotic liver tissue might result in elevated FVIII synthesis [ 178 ].…”
Section: Possible Interaction Mechanisms Among Coagulation Dyshomeost...mentioning
confidence: 99%
“…NAFLD, like other chronic liver illnesses, causes some individuals' fibrosis to worsen, which then causes cirrhosis and accompanying complications. 4 The majority of individuals can die from cardiovascular disease and metabolic syndrome since NAFLD and metabolic syndrome are closely related. In wealthy nations, obesity and NAFLD are widespread problems.…”
Section: Introductionmentioning
confidence: 99%